Effect of Severity Smooking on Thickness of Gingival Epithelium - Mohammed, Asam Kholifa; Suryono, Suryono; Sunarintyas, Siti (2012)
Smoking is one of the most important risk factor for oral diseases. Gingival protects underlying tissue. The thickness of oral mucosa epithelium is related with the amount of cell or proliferation activity. This study was aimed to investigate the effect of severity smoking on the thickness of gingival epithelium. This study used males Rattus norvegicus strain Spraque dawley, and were divided into 4 groups. They were control, mild, moderate, and severity smoker groups. The animal models were euthanized with ketamine in the 12th day. Gingival epithelium thickness was measured from basale layer to granular layer in 3 sites. The results were analyzed by one way anova. The result of this research showed there was increasing thickness of gingival epithelium of animal models. The conclusion of this study showed that severity smoker influenced the gingival epithelium thickness.